Tacit knowledge in craft pedagogy: a sociological analysis - Gamble, Jeanne (School of Education, 2023)
Though a very silent man he was so mild and calm that Ged soon lost his awe of him, and in a day or two he was bold enough to ask his master 'When will my apprenticeship begin, Sir?' 'It has begun', said Ogion. There was silence, as if Ged was keeping back something he had to say. Then he said it: 'But I haven't learned anything yet!' 'Because you haven't found out what I am teaching,' replied the mage. going on at his steady long-legged pace along their road ... From: The Earthsea Quartet, by Ursula /e Guin This thesis explores the relationship between tacit knowledge and a pedagogy that centres round a master-apprentice relationship, in order to locate tacit craft knowledge within a broader taxonomy of knowledge forms and their transmission practices. By its own definition tacit knowledge constitutes a unique class of phenomenon, namely that which is not presentable in language. It is thus a difficult concept to grasp and an even more difficult concept to represent in words. Evidence from a single qualitative case study on craft transmission practices m the institutional training centre of the Furniture Industry Training Board (known as the 'trade school') in Cape Town is presented and analysed in accordance with a conceptual scheme that derives from the earlier work of Basil Bernstein. Against the background of this analysis of craft pedagogy, the nature of the 'tacit' is explored through a detailed analysis of the evaluative requirements of the final trade test. Thereafter a conceptual model is developed to provide a theoretical explanation for the form that tacit craft knowledge takes. The findings show that strong external 'classification' and 'framing' relations (terms developed by Bernstein) constitute the trade school as a specialised context that is temporarily insulated from the work practices of mass production factories. It is a particular relation between work organisation, tool and materials usage, that retains the traditional craft or trade of cabinet making as the 'identity' recognised as legitimate in the trade school. Internal 'framing' displays two modalities. While strong macro pacing that resembles the daily routine in a factory is maintained throughout the five stages of the apprenticeship II curriculum, very weak initial framing over selection, sequencing and mtcro pacing allows apprentices to develop their own rhythms of work and to make their own decisions about task realisation. However, just before the end of the final stage and before apprentices take their final trade test framing over selection, sequencing and pacing is strengthened and made explicit. Evaluation criteria are very strongly framed in all stages of the apprenticeship curriculum. In terms of the regulative discourse of the trade school the master-apprentice relation is undoubtedly an asymmetrical relation that is mediated through a surrogate kinship role taken on by the master-trainer to exercise a form of positional control. The qualities of character and conduct that are transmitted are those of the autonomous artisan representing a collective craft tradition. The outcome of a strongly classified and framed craft pedagogy that centres round a masterapprentice relationship is found to be an external performance that is grounded or embedded in an internally held competence. Such internalised competence refers to a capacity for visualisation that acts as a proxy for a relationship between 'parts' and 'whole' that cannot be rendered in words. This relationship is held in the body and constitutes what can be called the 'tacit' in craft. The identity of the craft worker or 'tradesman' rests crucially on this combination of external performance and internalised time-space relation. Given this understanding of craft it becomes possible to describe craft as a restricted form of context independent 'knowledge' rather than merely as 'skill'. The conceptual model that is developed in the later part of the thesis locates craft as a form of knowledge that is independent of context in the sense that all craft knowledge realises an order of relation between the features of the object being made that is given by a particular embodied principle of arrangement. It is on this basis that craft takes its place in a systematic taxonomy of knowledge forms, which, although functioning at a fairly high level of abstraction 1s, nevertheless consistent with the empirical findings of the study. Implications of thesis findings and conclusions for an understanding of knowledge and pedagogy more generally are presented in the final chapter.